High-cycle fatigue behavior of temporomandibular joint implant - Arabshahi, Zohreh (2013)
The Temporomandibular Joint (TMJ) is a unique joint in the body which has a frequency of motion up to 2000 times per day. There are many TMJ disorders which can disable the joint leading to implantation of TMJ implant. Long-term follow-up of patients with TMJ implant needs to be studied for the benefit of both patients and clinicians. During the jaw movement, TMJ is subjected to varying loads which could cause fatigue failure of TMJ implant at high loading cycles. Therefore, it is important to ensure that TMJ prosthesis is protected against fatigue failure which indicates its long-term success. The aim of this study is to examine the fatigue analysis of three TMJ implants made of titanium alloy, cobalt-chromium alloy and stainless steel 316L, using finite element method. A three-dimensional model of mandible consisting of cortical and cancellous bone was developed from computed tomography images. A basic TMJ implant and fixation screws were modeled using three-dimensional modeling software. Finite element analysis of implanted mandible was done by assigning forces simulating the masticatory muscles to represent five static biting tasks. The loading configurations consisted of nine principal masticatory muscles. The results of static analysis showed that the resultant equivalent stresses in TMJ implant did not exceed the respective material’s yield stress. The safety factor of all three materials was larger than 1, which indicates sufficient strength for the five simulated clenching tasks. The Fatigue analysis showed that all three materials will never fail under fatigue. Titanium showed the best performance as it has the higher safety factor to ensure long-term success of a TMJ implant.